Wpływ liniowo sprężystego odciążenia na parametry ruchu sztywnej płyty spoczywającej na sprężysto-plastycznym gruncie - Włodarczyk, E. (Engineering Transactions, 1969)
In the paper presented the problem of the motion of a rigid plate resting upon an elastoplastic medium with an elastic unloading is solved. The plate was loaded uniformly with a pressure suddenly applied and subsequently decreasing monotonously to zero. The problem of the unloading wave is solved here in the following manner. The pressure (stress) under the plate of the segment of unloading (obtained from the exact solution), beginning from the value equal to the plasticity limit, was approximated by a «stepping» line. With such an approximation the problem of lightening was solved explicitly. An accurate numerical analysis of the problem was carried out and it was found that the model of a body with a rigid unloading can be applied in practical calculations in the case in which the coefficient of rigid lightening μ2 = a2/a1 > 5. When the above inequalities are satisfied, the errors resulting from approximation of the real elastoplastic medium by the model with rigid unloading do not exceed a few percent.